Technical Comparison Between Classical and Quantum Architectures: Quantum Error Challenges and Qubit Stability - Bonie Wijaya; Muhammad Fahrizal; Muhrodi; Dhamma Nagara; Yan Everhard (Universitas Pamulang, 2024)
The age of evolving computational technologies, classical architecture (traditional digital computing) and quantum architecture have emerged as two prominent approaches, offering diverse computational solutions. Classical computing bases its operations on transistors and binary logic gates, while quantum computing leverages the principles of quantum mechanics to perform information processing. This article provides a technical comparison between the two architectures, encompassing essential characteristics, algorithms, processing models, problem-solving capabilities, and challenges faced. In particular, this article highlights the key challenges in quantum computing, namely quantum errors and qubit stability, which significantly impact its reliability and practical implementation. The method used in this research is a literature review study, analyzing various reference sources such as journals, articles, and research reports. With the growing influence of quantum computing in specific sectors, this study is expected to provide a clearer view of the potential and limitations of both architectures, as well as the steps needed to overcome these challenges. The main conclusion of this study is that quantum computing has the potential to revolutionize certain fields, but still faces challenges in terms of stability and error correction.